ANALISIS PENGARUH TINGKAT EFISIENSI TERHADAP TINGKAT KONSENTRASI INDUSTRI JAMU INDONESIA - Mythyson Jimmy Nainggolan (Jurnal Ekonomi Pembangunan, 2012)
This final research is entitled, â€œAn Analysis of the Influence of Efficiency Level on the Herbal Drinking (Jamu) Industry Concentration Level in Indonesia.â€ This research was intended to identify the jamu industry concentration level during the pre economic crisis and after economic crisis and want to know the influence of efficiency level on the jamu industry concentration level. The secondary data included those collected from publications by Central Statistics Bureau, Jamu Producers Association, and Ministry of Industry and Trading and those of the sources such as research journals, newspapers, magazine and reviews of the literature. Analysis technique is used descriptive analysis qualitative and quantitative. The research results show that before and economic crisis jamu industry was marked by the average concentration level of 77 percent and the average value of concentration level after the crisis, it lowered to 67 percent. The regression computation showed that the efficiency level influenced significantly on that of concentration as shown by the R-Square value of 27,50 pecent. Keywords: Efficiency and Concentration Level.